Nanoscale devices : physics, modeling, and their application - Kaushik, Brajesh Kumar (Boca Raton : Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa, plc, 2019)
The primary aim of this book is to discuss various aspects of nanoscale device design and their applications including transport mechanism, modeling, and circuit applications. Furthermore, the book develops a strong foundation to understand the need for moving from conventional MOSFET to novel devices, including, how the device physics and transport phenomenon changes with reduction in the device size to a nanoscale regime. Details about the simulation technique and/or fabrication process flow of the various nanoscale devices is included along with simulated results of device performance parameters. The numerical and theoretical methods are used to describe the related concepts.
OCLC-licensed vendor bibliographic record.
Keywords: Nanoelectronics; Nanoelectromechanical systems; Nanotechnology; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / Physics; TECHNOLOGY / Electronics / Microelectronics; TECHNOLOGY / Nanotechnology